Influence of Facebook brand-page posts on online engagement. Issue 4 (10th August 2015) - Luarn, Pin; Lin, Yu-Fan; Chiu, Yu-Ping
Abstract : Purpose: – The purpose of this paper is to examine how various characteristics of brand posts influence online engagement on Facebook brand pages. Design/methodology/approach: – The data used for this study were obtained from the posts of ten popular official brand pages. For the selected period between March 1 and May 1, 2014, a total of 1, 030 posts were obtained and manually processed on September 1, 2014. To assign post categories to the posts created by page administrators, the authors performed manual coding, following the coding development strategy. Findings: – The results demonstrated that the media and content type of posts exert a significant effect on user online engagement. This study used liking, commenting and sharing behavior as a measure of users' online engagement to specify the new phenomena. Originality/value: – The findings are relevant for the theory of information dissemination and provide valuable and directly applicable implications for the social media marketing of companies.